1980
DOI: 10.1084/jem.152.2.350
|View full text |Cite
|
Sign up to set email alerts
|

Mature bone marrow erythroid burst-forming units do not require T cells for induction of erythropoietin-dependent differentiation.

Abstract: Cell-cell interactions between mature T cells and peripheral blood null cells induce erythropoietin-stimulated differentiation of peripheral blood-derived erythroid progenitors. By the use of complement-fixing cytolytic murine hybridoma and antibody uniquely reactive with mature T lymphocytes, this dependence of immature peripheral blood erythroid burst-forming unit (BFU-E) differentiation upon mature T cells or a T cell conditioned medium is confirmed. By using the same antibody, it is demonstrated that the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1

Year Published

1981
1981
1992
1992

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 29 publications
2
23
1
Order By: Relevance
“…1) are consistent with the concept that the mature erythroid stem cells (CFU-E) can proliferate in the absence of T cells (25). CFU-E numbers were, in fact, increased after T cell depletion in normals, which may reflect some enrichment of CFU-E by the separation procedure.…”
Section: Methodssupporting
confidence: 71%
“…1) are consistent with the concept that the mature erythroid stem cells (CFU-E) can proliferate in the absence of T cells (25). CFU-E numbers were, in fact, increased after T cell depletion in normals, which may reflect some enrichment of CFU-E by the separation procedure.…”
Section: Methodssupporting
confidence: 71%
“…In further studies, they have indicated that T helper function for erythropoiesis was not deficient in their patients with congenital hypoplastic anemia (14). However, it is presently unclear whether T helper cells are even required for normal bone marrow, rather than peripheral blood, erythroid colony growth (18). In our own patients, addition of normal peripheral blood mononuclear cells to patients' bone marrows in erythroid cultures failed uniformly to improve the poor erythroid colony growth of the patients, arguing against a helper cell defect in our patients, and supportive of an intrinsic proliferative defect.…”
Section: Discussionmentioning
confidence: 99%
“…A complex T cell network has been found to regulate the immune response in man (53) and considerable data have implicated what is believed to be a T lymphocyte as an inducer of erythroid differentiation (5,6,29,54,55). In addition, normal Ty cells have been shown to suppress in vitro erythroid (6,36) and granulocyte (56) colony expression.…”
Section: Discussionmentioning
confidence: 99%